Crystal structure of N-((3s,5s,7s)-adamantan-1-yl)-2-(3-benzoylphenyl)propanamide, C26H29NO2 - Gao Li-Na; Gu Ye; Jin Feng; Hao Duo; Zhang Xin-Ru (Zeitschrift für Kristallographie - New Crystal Structures)
C26H29NO2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 10.8490(8) Å, b = 13.2892(9) Å, c = 14.7199(10) Å, α = 89.161(3)°, β = 79.991(2)°, γ = 85.746(2)°, V = 2084.2(3) Å3, Z = 4, R gt(F) = 0.0641, wR ref(F 2) = 0.1449, T = 170 K.